Uso de la pulpa de pescado en la alimentación de híbridos de tilapia (Tilapia homorum macho y Tilapia mossambica hembra) cultivados en jaulas en Puntarenas, Costa Rica - Blanco B., Oscar; Román G., Tobías (Revista de Biología Tropical, 1986)
From March to July 1985, six species of shrimp by-catch ichthy ofauna from the Nicoya Gulf, Costa Rica were processed to feed tilapia hybrids (T. homorum, male and T. mossambica, female) in a system of floating cages. The weight gain and feed conversion is 1.8 kg; meanwhile, in the control it is of 2.4 kg.